Profile of Nonvolatile Compounds and Their Correlation to the Flavor of Fried Shallots - Yofananda, Olivia; Wijaya, Christofora Hanny; Lioe, Hanifah Nuryani; Sobir, Sobir (Department of Technology of Agricultural product (THP) Jambi University, 2025)
This study aimed to evaluate the relationship between the nonvolatile compounds detected in fried shallots and their sensory characteristics. Six shallot varieties were used: Bima Brebes, Bauji, Tajuk, Super Philip, Batu Ijo, and Rubaru. Each variety was assessed using the rate-all-that-apply (RATA) and hedonic rating tests for the taste and aroma of fried shallots. All fried shallots were prepared in a laboratory under homogeneous frying conditions. The chemical compounds in the water extracts of the six fried shallots with molecular weights less than 3 kDa were identified using LC-MS/MS instrument. Additionally, the correlation between the chromatographic peak intensities of the chemical compounds and sensory intensities was examined through multivariate orthogonal partial least squares (OPLS) analysis. The PCA result revealed two distinct groups of samples. Batu Ijo fried shallot, which received the highest overall hedonic score and showed a strong correlation between its fragrant sulfury aroma and savory taste, was categorized separately from the others. Although 18 compounds were identified in fried shallots, a significant correlation was observed only with salty taste, primarily due to glutamyl-phenylalanine, a known kokumi compound.